2010
DOI: 10.1002/ejlt.201000022
|View full text |Cite
|
Sign up to set email alerts
|

PFG‐NMR on W1/O/W2‐emulsions: Evidence for molecular exchange between water phases

Abstract: A major question in the investigation of multiple emulsions of WOW-type is that of stability and ripening, which is often reflected in the droplet-size distribution (DSD). The DSD is an important parameter for judging product properties. Instability in multiple emulsions is often linked to molecular exchange between inner and outer water phases (W 1 , W 2 ), which has to be taken into account. For example, coalescence phenomena and Ostwald ripening affect microscopic and/or macroscopic stability and therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…However, deviations from the expected behaviour are observed for W 1 /O/W 2 emulsions in several publications. [87][88][89][90][91] The observations are consistently described by a model that takes the exchange of molecules between the water phases into account. This phenomenon was described in the context of NMRexaminations of tissue.…”
Section: Double Emulsionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, deviations from the expected behaviour are observed for W 1 /O/W 2 emulsions in several publications. [87][88][89][90][91] The observations are consistently described by a model that takes the exchange of molecules between the water phases into account. This phenomenon was described in the context of NMRexaminations of tissue.…”
Section: Double Emulsionsmentioning
confidence: 99%
“…The interpretation was confirmed by exploiting driven diffusion. [88] Independent evidence of the molecular exchange between the inner and outer water phase in WOWdouble emulsions was obtained using CLSM images. It is obvious that the diffusion and exchange properties across the oil depend on the recipe, i.e.…”
Section: Double Emulsionsmentioning
confidence: 99%
“…In several publications, the possibility of molecular exchange in double emulsions is discussed [5][6][7][8][9][10][11][12] . In some publications [8][9][10] , a molecular exchange model was applied, which originally was found to be applicable in case of cellular systems [5][6][7] .…”
Section: Diffusion Phenomena Between W 1 and W 2 In W 1 /O/wmentioning
confidence: 99%
“…One argument against the exchange hypothesis is that the solubility of the two substances is low and they tend to separate when mixed. To find out if and on which time scale diffusion between W 1 and W 2 takes place 11 , the idea was to add a small amount of Xanthan to W 2 . Xanthan is a common thickener, also used in food industry.…”
Section: Diffusion Phenomena Between W 1 and W 2 In W 1 /O/wmentioning
confidence: 99%
“…We have recently shown that molecular transport of water molecules through the oil layer of W/O/W emulsions can be detected using diffusion NMR 2 . This type of water transport became more important when raising the measurement temperature and NMR diffusion delay time D. Our previous results have also shown that water transport in double emulsions with large oil globule sizes (about 50 µm in diameter) mainly occurred between the inner water phase and the oil phase 2 , whereas other authors 3,4 described the exchange between the internal and external water phase. Therefore, it is interesting to evaluate whether the oil globule size of the W/O/W emulsion might explain the difference in observed water transport mechanism.…”
Section: Introductionmentioning
confidence: 77%